The Influence of Government Expenditures in the Education and Health Sectors on the Human Development Index and Its Impact on the Open Unemployment Rate in Pontianak City for the 2010-2022 Period - Romadoni; Verdianti; Firman (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research was conducted with the aim of analyzing the influence of the government budget in the education and health sectors on the Pontianak City Human Development Index (HDI), as well as the influence of the Pontianak City government budget in the education, health and Human Development Index (HDI) sectors on unemployment in Pontianak City in 2010 – 2022. The analytical method used is path analysis using secondary data sourced from the Directorate General of Financial Balance (DJPK) and the Pontianak City Central Statistics Agency. The results of this study found that the education and health sector budgets had an influence and significance on the Human Development Index (HDI) of Pontianak City, and the Pontianak City government budget for the education and health sectors had an influence but was not significant on the level of open unemployment in Pontianak City, as well as the HDI ( Human Development Index) has an effect but is not significant on the level of open unemployment. The results of the F test found that together the education and health sector budgets had a significant influence on the Human Development Index and together the Pontianak City government budget for the education, health sectors and the Human Development Index (HDI) had a significant influence on the level of open unemployment.